A internação psiquiátrica compulsória : uma abordagem à luz dos direitos fundamentais - Monteiro, Fábio de Holanda (2015)
This dissertation aims at analyzing the compulsory psychiatric hospitalization of people with mental disorders from the perspective of fundamental rights. The controversies surrounding this admission mode are not restricted to the deprivation or restriction of the freedom of individuals treated by mandatory hospitalization, but also in relation to other fundamental rights involved, such as health and patient safety, their families and society. It is observed that the confrontation between fundamental rights surrounding the compulsory hospitalization require consideration of the case, with the use of proportionality and weighting values, seeking to adopt a more consistent solution with respect to the principle of human dignity so that compulsory inpatient measure be considered constitutional orientation within the Brazilian legal system. The national legal system, and more particularly, the provisions orienting fundamental rights under the Federal Constitution of 1988, as well as the ones within the Brazilian Psychiatric Reform Law were taken as reference. Some national and international case law related to the topic studied, as well as the relevant doctrine, establishing, through a transdisciplinary approach, the interface with the Law, were also addressed.As a preparatory step to a better understanding of compulsory hospitalization and fundamental rights of people with mental disorders, the choice was made on the discourse on the historical evolution of the disease and mental health, highlighting the difficulty that persists to this day in being precise in its definitions. It also addresses the principal international standards related to the rights of psychic disorders patients and the major foreign psychiatric reform movements that influenced the Brazilian Psychiatric Reform. In order to establish a counterpoint to foreign law, the Argentine, Spanish and Portuguese legislation are addressed, in its most relevant points related to involuntary admission (compulsory). Finally, the main legal instruments aimed at giving legal protection to the fundamental rights of people with mental disorders subject to compulsory hospitalization are checked.